Intravitreal bevacizumab-induced exacerbation of proteinuria in diabetic nephropathy, and amelioration by switching to ranibizumab. (February 2020) - Hanna, Ramy M; Abdelnour, Lama; Hasnain, Huma; Selamet, Umut; Kurtz, Ira
Certain diabetic and hypertensive patients started on intravitreal vascular endothelial growth factor inhibition for diabetic retinopathy may experience worsening of hypertension and proteinuria. The etiology of this is the newly recognized absorption of intravitreally injected vascular endothelial growth factor inhibitors, and the susceptibility of patients with pre-existing renal disease to exacerbations depends on the degree of systemic absorption. There are eighteen reported cases of worsening hypertension, woresening proteinuria, worsening renal function, thrombotic microangiopathy, and glomerular disease noted after initiation of intravitreal vascular endothelial growth factor blockade. This nineteenth case demonstrates worsening hypertension and proteinuria with the start of bevacizumab. Both blood pressure and proteinuria parameters showed overall improvement with switching to the less absorbed and lower potency agent ranibizumab. There was a slight rise in serum creatinine after bevacizumab therapy, which stabilized at a new baseline, and the serum creatinine remained stable on ranibizumab. There were no other nephrotoxic exposures that explained the mild rise in serum creatinine. Because of improvement in renal function and proteinuria, a renal biopsy was deferred for the time. This case re-demonstrates the risk of worsening proteinuria with vascular endothelial growth factor inhibitors when given intravitreally in some patients. The demonstration of improvement in blood pressure and proteinuria with the use of lower potency agents like ranibizumab is novel and an important concept confirming observations from pharmacokinetic studies. The switch to ranibizumab offers a therapeutic option when proteinuria worsens with intravitreal vascular endothelial growth factor blockade, and the patient requires ongoing intravitreal therapy for treatment of diabetic retinopathy.